Hao-Fountain syndrome and genital disorders: report of a new possible association - Nicola Zampieri; Rebecca Pulvirenti; Eleonora Pedrazzoli; Francesco Saverio Camoglio (BMC, 2022)
Abstract Background Hao-Fountain syndrome is a neurodevelopmental disorder characterized by global developmental delay, variably impaired intellectual development with significant speech delay and, in some males patients, it has been reported an association with hypogonadism. At present less than 50 cases are reported in literature. Case presentation We report a case of this rare syndrome in a young female with isolated tubal torsion; our patients had different hospitalizations without treatment but during the last episode we decide to perform an abdominal surgical explortion. This is the first case in Literature with a new USP7 mutation. Conclusions This case opens new perspective in this rare syndrome and a review approach to isolated tubal torsion. These symptoms should be always well checked.